2021
DOI: 10.1111/ajo.13368
|View full text |Cite
|
Sign up to set email alerts
|

Abortion education in Australian medical schools

Abstract: This aim of this study was to gain an updated perspective of the teaching and learning experiences of abortion care among Australian medical students. All 2020 Australian final‐year medical students were invited to complete a 12‐question cross‐sectional electronic survey. While it appears that abortion care is taught in most Australian medical schools, in some it is not, and where the topic is presented, structured and standardised teaching is still lacking. Students’ confidence around abortion care once they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…In Canadian medical schools, lack of discussion of both the epidemiology of abortion and how best to counsel pregnant patients about their options has resulted in students graduating from medical school with a poor understanding of every aspect of abortion, from the clinical to the social to the epidemiological (Cessford & Norman, 2011). In Australia, where abortion is taught in most medical schools, newly graduated physicians still express little confidence in their ability to provide abortion care; consequently, Australian medical students have called for more exposure to abortion during medical training (Cheng & deCosta, 2021). In Argentina, although most final‐year medical students know that abortion is restricted in Argentina, they still harbor misconceptions about when abortion is permitted, indicating that abortion is inadequately addressed in the medical school curricula.…”
Section: Learning About Abortion In Medical Schoolmentioning
confidence: 99%
See 1 more Smart Citation
“…In Canadian medical schools, lack of discussion of both the epidemiology of abortion and how best to counsel pregnant patients about their options has resulted in students graduating from medical school with a poor understanding of every aspect of abortion, from the clinical to the social to the epidemiological (Cessford & Norman, 2011). In Australia, where abortion is taught in most medical schools, newly graduated physicians still express little confidence in their ability to provide abortion care; consequently, Australian medical students have called for more exposure to abortion during medical training (Cheng & deCosta, 2021). In Argentina, although most final‐year medical students know that abortion is restricted in Argentina, they still harbor misconceptions about when abortion is permitted, indicating that abortion is inadequately addressed in the medical school curricula.…”
Section: Learning About Abortion In Medical Schoolmentioning
confidence: 99%
“…Abortion is common in other countries too—one in three women in the United Kingdom have an abortion before age 45 (Cohen et al, 2021). In Australia, a country of about 25 million people, physicians perform 100,000 abortions annually (Cheng & deCosta, 2021), Although legal restrictions regarding abortion now vary in South American countries, between 1995 and 2008, when abortions were almost exclusively illegal, 25% of all pregnancies nevertheless ended in abortion (Provenzana‐Castro et al, 2016; Sedgh et al, 2012). Worldwide today, between 40 and 50 million abortions are performed annually (Adekanye, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Student curricula need to focus on clinical delivery of abortion services, not only ethical and legal dimensions 9 . With the majority of abortion service provision currently occurring outside of hospitals in private community‐based services, student placements and skills‐focused training in high volume community‐based clinics need to be supported.…”
mentioning
confidence: 99%
“…Induced abortion is presumably one of the most common gynaecological procedures in Australia, with an estimate of at least 100 000 abortions performed annually 1 . We can only approximate the abortion rate as there is no national data collection on induced abortion.…”
mentioning
confidence: 99%
“…The demand to have mandatory education on abortion as part of the curriculum aligns with the views of Australian medical students. A study of Australian final year medical students found that around 80% reported inclusion of abortion care education in their curriculum; 1 however, very few had direct exposure in an abortion clinic. All of those who did not receive any teaching on abortion would like this subject covered in the curriculum.…”
mentioning
confidence: 99%